Evaluation of Liquefaction Potential Through Geophysical Tests Case - (:unkn) unknown (Springer Nature Switzerland, 2024)
On May 26, 2019, at 02:41 h (Peruvian time), the Mw 8.0 Sismo Lagunas 2019 earthquake occurred. It had its epicenter at the coordinates: − 05.74°, − 75.55°, 60 km south of the town of Lagunas (Loreto), at a depth of 135 km with Mw 8.0. It caus...
Keywords: Licuefacción; Geofísica